Engineering protein folding and translocation improves heterologous protein secretion in Saccharomyces cerevisiae. Issue 9 (30th June 2015) - Tang, Hongting; Bao, Xiaoming; Shen, Yu; Song, Meihui; Wang, Shenghuan; Wang, Chengqiang; Hou, Jin
ABSTRACT Saccharomyces cerevisiae is widely used as a producer of heterologous proteins of medical and industrial interest. Numerous efforts have been made to overcome bottlenecks in protein expression and secretion. However, the effect of engineering protein translocation to heterologous protein secretion has not been studied extensively in S. cerevisiae. In this work, we confirmed that heterologous protein expression in S. cerevisiae induced the unfolded protein response (UPR). To enhance protein folding capacity, the endoplasmic reticulum (ER) chaperone protein BiP and the disulfide isomerase Pdi1p were each over‐expressed, and the secretion of three heterologous proteins, β‐glucosidase, endoglucanase, and α‐amylase, was improved. The impact of engineering key translocation components was also studied. The over‐expression of co‐translational translocation components Srp14p and Srp54p enhanced the secretion of three heterologous proteins (β‐glucosidase, endoglucanase, and α‐amylase), but over‐expressing the cytosolic chaperone Ssa1p (involved in post‐translational translocation) only enhanced the secretion of β‐glucosidase. By engineering both co‐translational translocation and protein folding, we obtained strains with β‐glucosidase, endoglucanase, and α‐amylase activities increased by 72%, 60%, and 103% compared to the controls. Our results show that protein translocation may be a limiting factor for heterologous protein production. Biotechnol. Bioeng. 2015;112: 1872–1882. © 2015 Wiley Periodicals, Inc.